THE CONCEPT OF DISCOURSE IN MODERN LINGUODIDACTICS - Holdorova Gulzhakhon Shavkatjon kizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article discusses and analyzes the works related to the disclosure of the essences of linguodidactics, discourse, discursive competence, the formation of discursive competence among students of secondary schools of grades 7-9. Theoretical and practical works were considered in order to reveal the degree of scientific development of the topic, including the concepts of linguodidactics, discourse, American, French, Russian schools of discourse, discursive competence. According to the author, the need to form the communicative competence of schoolchildren in oral speech brings discursive competence to the fore as one of its most important structural component. The article emphasizes that the formation of discursive competence is one of the practical goals of modern education and an important condition for the effectiveness of oral communication, on the basis of which school students can exercise their communicative abilities in various communication situations.